Efficacy of minimally invasive vascular interventions assessed with mobile multispectral near-infrared spectroscopy - Alisha Roberta Oropallo, MD; Amit Rao, MD; Jo Ann Eisinger, PA; Larry Leonardi, PhD (JVS-Vascular Insights)
Background: The adoption of minimally invasive techniques for treating chronic venous insufficiency has surged. Techniques such as foam sclerotherapy and radiofrequency ablation (RFA) are now widely used to address incompetent great saphenous veins. Duplex ultrasound examination has become the gold standard for diagnosing venous insufficiency and evaluating the effectiveness of these treatments. However, venous reflux ultrasound studies remain some of the most time-consuming tasks to obtain. Objective: The objective of this study was to evaluate the effectiveness of minimally invasive vascular interventions, such as foam sclerotherapy and/or RFA, using mobile multispectral near-infrared spectroscopic (NIRS) imaging. By measuring changes in tissue oxygenation (StO2) before and after treatment, this study aims to provide insights into the utility of NIRS imaging as a noninvasive tool for assessing treatment outcomes. Methods: This quasi-experimental pre-post-test design study included 14 patients treated for chronic venous insufficiency with either foam sclerotherapy or RFA between November 2022 and February 2024. The patient population presented with significant great saphenous vein insufficiency and normal deep venous pathology, with no evidence of deep vein thrombosis or superficial vein thrombosis, except for one case with partial chronic and deep venous thrombosis. NIRS images of the lower extremities were collected before and immediately after the treatment. The images were acquired from various anatomical locations including the dorsum and plantar aspects of the foot, the medial and lateral leg, and the wound area if present. Results: The results demonstrated a statistically significant increase in mean StO2 in lower extremities after foam sclerotherapy and RFA, indicating an improved microcirculatory function in the treated limb. These improvements in StO2 in the lower extremities were consistent with the vascular examination results, which confirmed successful vein ablation or closure. Conclusions: The study demonstrates that NIRS imaging effectively tracks treatment-related changes, providing a noninvasive and reliable method for the real-time assessment of StO2. By visualizing changes in microcirculation, this technology offers clinicians valuable insights, enabling earlier detection of treatment success or failure and facilitating timely interventions. As such, NIRS imaging holds promise as a valuable tool in clinical practice for evaluating the efficacy of minimally invasive vascular treatments. However, the small sample size limits the ability to draw definitive conclusions.